VD_FINDINFO Arrêt / 2025 / 415 vom 10. Juni 2025 - VD Tribunal cantonal (2025)
AIASSURANCE, NOUVELLE DEMANDE, EXPERTISE | 28 al. 1 LAI, 29 al. 1 LAI, 4 al. 1 LAI, 6 LPGA, 7 LPGA, 8 LPGA, 87 al. 2 RAI, 87 al. 3 RAI